Digital Beam Forming Concepts with Application to Spaceborne Reflector SAR Systems - Huber, Sigurd; Younis, Marwan; Patyuchenko, Anton; Krieger, Gerhard (International Radar Symposium (IRS), 2010)
The trend in the conception of future spaceborne radar remote sensing is towards the use of Digital Beam Forming (DBF) techniques. These systems will comprise multiple digital channels, where the analog-to-digital converter is moved closer to the antenna. This dispenses the need for analog beam steering and by this the use of transmit/receive modules for phase and amplitude control. Digital beam forming will enable Synthetic Aperture Radar (SAR) which overcomes the coverage and resolution limitations applicable to state-of-the-art systems. Moreover, new antenna architectures, such as reflectors, already implemented in communication satellites, are being reconsidered for SAR applications. This paper is dedicated to the digital signal processing aspects of such reflector based SAR systems. After introducing the hardware concepts the beam forming algorithms are presented and demonstrated by means of numerical simulations.
DLR Import::2019-04-03